Strategies for Promoting Energy Literacy in Physics Education: Insights from a Systematic Literature Review - Sriatun, Neng; Ardianto, Didit; Irvan Permana; Afriana, Jaka (Journal of Innovative Science Education, 2025)
In physics education, fostering energy literacy is essential to equip students with the skills needed to navigate resource scarcity and environmental issues. By developing energy literacy, students are better prepared to manage energy consumption in a sustainable and sustainable manner. This research aims to explore effective strategies and approaches to improve students' energy literacy through the Systematic Literature Review (SLR) method. The study analyzed academic papers from reputable sources such as ScienceDirect, Taylor & Francis, Springer Nature, and ERIC, with a focus on publications from 2020 to 2024. Using keywords such as "energy literacy", "high school students", and "education", this analysis uncovers five main themes: student energy literacy, learning processes, social-scientific exhibitions, teaching modules, and learning media. Most research centers on understanding how students understand the concept of energy and what factors influence their understanding. Successful teaching strategies, including the use of social-scientific exhibitions to raise awareness of energy issues, as well as the development of energy-focused and sustainability-based teaching modules, were found to significantly improve student understanding. In addition, the use of technology-based learning tools has proven effective in conveying complex energy concepts. These findings point to new avenues for research, especially in integrating local wisdom into energy education. This study offers a new perspective on how incorporating local knowledge can improve energy literacy and deepen student engagement with sustainability efforts.